Numerical Approximation of Acoustic Equation using Radial Basis Function-discontinuous Galerkin Method. (2017) - Kresno, W.S.; Wardani, S.P.R.; Susila, Endra; Pranowo,
Abstract: Acoustic equation is an important equation in order to determine wave propagation in a medium. The Application of acoustic equations vastly known, i.e. elastic wave propagation, fluid dynamics and gas dynamics equivalent. This paper present Radial Basis Function - Discontinuous Galerkin Method (RBF-DGM) in order to solve acoustic equation. RBF-DGM method is a numerical method, proposed to solve partial differential equations (PDE). RBF-DGM approximated the space domain with RBF and using DGM for time integration method. RBF-DGM application presented then in order to solve acoustic equation. The numerical of RBF-DGM presented, and compared with analytical solution as a result. The numerical results, show that the RBF-DGM (linear) predicting the exact results or analytical well.